Flexibility and security in the labour market: An analysis of the governance of inequality - Colin Crouch (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2010)
The financial crisis drew attention to the way in which workers in certain countries had been able to sustain consumption through housing and consumer credit despite insecure labour-market positions. This indicates a need to expand the analysis of the relationship between flexibility and security in labour markets beyond the normal scope of labour and social policy to include many other aspects of not only public policy but also corporate practice that affect that relationship. Individuals are seen as based within a number of collectivities within which life chances are collectively determined (or CLCs). These collectivities are subject to various forms of governance. Finally, attention is given to the dimension of sustainability, the capacity of any combinations of policies and practices to endure self-destructive tendencies. The governance mechanisms of CLCs are then seen as using one or more strategies for achieving a certain balance between uncertainty and security: externalization of risk on to other CLCs; postponement of risk-bearing to future periods of time; externalization of risk on to certain members of the CLC itself; widespread sharing within the CLC. This approach is then used to consider the main policies and practices relevant to the field: employment law; social policies directly delivering services; advancement of skill and employability levels available within the population; public promotion and/or protection of sectors and production locations perceived to be of strategic importance, including public employment; government demand management; insurance and pensions; trading relationships among nation states with different export and import patterns; consumer credit to sustain mass consumption; locally clustered economic sectors; the shadow economy; managerial organization of activities offering varying degrees of security among different countries and regions, including supply chain management; internal labour markets and organization of work and work roles; collective bargaining; inter-generational transfers and support; the protection of property-owning elites from labour-market uncertainty.
Keywords: 330; Arbeitsmarkt - Flexibilität; soziale Ungleichheit; Governance; Arbeitsmarktpolitik; nachhaltige Entwicklung; soziale Sicherheit; Arbeitsrecht; Sozialpolitik; Beschäftigungsfähigkeit; öffentlicher Dienst; Rentenversicherung; Handel; Kredit; Beschaffung; interner Arbeitsmarkt; Tarifverhandlungen; Wissenstransfer; Flexicurity